Facile Synthesis and Proposed Mechanism of α, ω‐Oxetanyl-Telechelic Poly(3-nitratomethyl-3-methyl oxetane) by an SN2(i) Nitrato Displacement Method in Basic Media. Issue 1 (2nd January 2017) - Desai, Hemant J.; Acheampong, Daniel O.; Hudson, Robert; Lacey, Richard; Stanley, Claire; Turner, Helen; Whitmore, Hannah; Torry, Simon; Golding, Peter; Erothu, Harikrishna; Topham, Paul
ABSTRACT: The synthesis of a novel heterocyclic–telechelic polymer, α, ω-oxetanyl-telechelic poly(3-nitratomethyl-3-methyl oxetane), is described. Infrared spectroscopy (IR), gel permeation chromatography (GPC), and nuclear magnetic resonance (NMR) spectroscopy have been used to confirm the successful synthesis, demonstrating the presence of the telechelic-oxetanyl moieties. Synthesis of the terminal functionalities has been achieved via displacement of nitrato groups, in a manner similar to that employed with other leaving groups such as azido, bromo, and nitro, initiated by nucleophiles. In the present case, displacement occurs on the ends of a nitrato-functionalized polymer driven by the formation of sodium nitrate, which is supported by the polar aprotic solvent N, N -dimethyl formamide. The formation of an alkoxide at the polymer chain ends is favored and allows internal back-biting to the nearest carbon bearing the nitrato group, intrinsically in an SN 2(i) reaction, leading to α, ω-oxetanyl functionalization. The telechelic-oxetanyl moieties have the potential to be cross-linked by chemical (e.g., acidic) or radiative (e.g., ultraviolet) curing methods without the use of high temperatures, usually below 100°C. This type of material was designed for future use as a contraband simulant, whereby it would form the predominant constituent of elastomeric composites comprising rubbery polymer with small quantities of solids, typically crystals of contraband substances, such as explosives or narcotics. This method also provides an alternative approach to ring closure and synthesis of heterocycles.